Arterial thrombosis and cancer. Issue 164 (April 2018) - Aronson, Doron; Brenner, Benjamin
Abstract: Cancer-associated arterial thrombotic events (ATEs) are increasingly recognized in specific malignancies and in association with the expanding armamentarium of novel chemotherapeutic agents. The improved cancer survival led to cardiovascular complications becoming clinically relevant many years after cancer diagnosis. The pathobiology of ATEs in cancer is complex and the individual patient risk for an ATE entails a multifactorial interaction between the traditional cardiovascular risk factors and comorbidities, the specific malignancy and selected therapy. Treatment with several specific chemotherapeutic agents, immunomodulatory drugs, vascular endothelial growth factor pathway inhibitors, tyrosine kinase inhibitors, and radiotherapy, impart increased risk for ATEs that result from specific therapy-related mechanisms, often involving endothelial injury. Cancer cell-specific prothrombotic properties are important players in the pathogenesis of cancer-associated hypercoagulability. There are distinct biological and molecular processes preferentially activated in specific cancer cells which can trigger ATEs, including platelet activation, increased expression of procoagulants and suppression of fibrinolytic activity. ATEs portend adverse prognosis in cancer patients. Prevention and treatment of cancer-associated ATEs may be improved by greater awareness and careful monitoring for vascular toxicity, aggressive effort to optimize conventional cardiovascular risk factors, and use of antiplatelet and antithrombotic agents in selected patients. These issues are targets for future studies aimed to reduce ATEs in patients with cancer. Highlights: Arterial thrombotic events (ATEs) are increasingly recognized as an important complication of cancer and of novel chemotherapy. ATEs involves a complex interaction between the individual cardiovascular risk, the specific malignancy and selected therapy. Several immunomodulatory drugs, VEGF pathway inhibitors and tyrosine kinase inhibitors, impart increased risk for ATEs. Awareness of ATEs risk, careful monitoring and efforts to optimize risk factors are key for successful prevention. Judicious use of antiplatelet and antithrombotic agents may improve outcome in selected patients.